The Principle of Religious Tolerance in Basic Islam Harmony of Plural Society - Muhamad Amar Mahmad,; Mohd Nizho Abdul Rahman,; Azman Md Zain, (Journal of Islamic, Social, Economics and Development, 2018)
Religious conflict phenomenon happens is caused by a miscomprehension totalledabout issue sensitivity that exists in every religion. In dealing with this unconventionalatmosphere, scholars have agreed that tolerance in religion is the cure. Hence Islam takes agreat deal of consideration in this regard in parallel with it which is syllable. That includes allaspects and fields, including those relating to human relationships in spite of the differentreligions, races and languages. Islam is very concerned with harmony so it is always awake andforbid from elements that can lead to turbidity and fracture in the relationship. The main causethat leads to these split seeds is ethnocentrism and egoism that is thickened among every ethnicgroup. If every ethnicity does not manage the emotions well, the murky atmosphere will eruptat any time as has happened in the Middle East and so forth. This article attempts to highlightthe principle of tolerance outlined in Islam towards generating inner goodwill composed ofplural society. The method used in the writing of this article is the study of selected Quranicverses and the support of some of the scholarly views that are related to the subject of study.This highlight and analysis found that the principle of tolerance in Islam is very relevant to beapplied, especially in the Malaysian context of racial, religious and linguistic diversity.